• решить уравнение
    (x-2)(x+2)-(x-3)^2= - 1

    (x+1)^2-(x-2)(x+2)=7

Ответы 1

  • x²-4-(x²-6x+9)=-1    (x²+2x+1)-(x²-4)=7 x²-4-x²+6x-9=-1      x²+2x+1-x²+4=7 6x-13=-1                x²+2x+1-x²+4=7 6x=12                    2x+5=7x=2                        2x=2                               x=1 
    • Автор:

      jax5zdc
    • 5 лет назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years